Tradisi Beppa Apang di Bulan Ramadhan : Studi Komparatif Antara Nilai Qur’ani dan Perkara Bid’ah - Abdurrahman A (STAIN Majene, 2023)
This study aims to reveal the tradition of beppa apang which is a tradition of the Bugis community conducted on nisf ramaḍān, in terms of the form of tradition, the Qur'anic values contained in it and connecting it with the matter of heresy, this research is a field research that reveals the results with qualitative descriptiveness, by observation, interviews and documentation in data collection methods, the result is a form of beppa apang tradition some are carried out in the form of festivals and some are classic, namely with the mabbaca process before being distributed And eating together, there are many values of Qur'anic values, namely the value of silaturahmi, the value of da'wah and the value of sennung-sennungeng (tafāul) and this tradition is not a heresy or this tradition is not a misguided even though it can be said to be heresy then it is a heresy of maḥmūdah.